1965
DOI: 10.1037/h0022590
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic classification as a research tool.

Abstract: A two dimensional diagnostic classification plan was devised and put into operational use. One dimension indicates the kind of problem which was developed and worked on in counseling; the other dimension indicates the cause of the problem. An analysis of a college counseling case load over a 4 year period showed that vocational problems caused by lack of understanding of self constituted almost half of the total case load and that the nature of the case load was remarkably stable from year to year. The average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

1969
1969
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…Although there was a great deal of early interest in the field in developing taxonomies (Berezin, 1957;Bordin, 1946, Callis, 1965Campbell & Cellini, 1981) little has been done in the past few decades to provide practitioners with critical information about the types of career and psychological adjustment issues clients bring to counseling. In addition to the needs of practitioners, having this type of empirically validated taxonomy is critical in guiding research that can examine process and outcome with specific types of career clients and specific types of interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there was a great deal of early interest in the field in developing taxonomies (Berezin, 1957;Bordin, 1946, Callis, 1965Campbell & Cellini, 1981) little has been done in the past few decades to provide practitioners with critical information about the types of career and psychological adjustment issues clients bring to counseling. In addition to the needs of practitioners, having this type of empirically validated taxonomy is critical in guiding research that can examine process and outcome with specific types of career clients and specific types of interventions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Bordin (1946) focused on this concern in the 1940s and developed one of the first diagnostic systems based on psychodynamic theory. Later Berezin (1957) and Callis (1965) developed a two-dimensional system with one dimension focusing on clients' problems and the other dimension identifying potential causes of the problem. In 1981, Campbell and Cellini published a taxonomy that identified four types of career problems.…”
mentioning
confidence: 99%
“…Seven a priori categories were identified that appeared to comprehensively cover the major reasons for career indecision and were relatively independent of each other. Three categories were derived from the cause dimensions of the Missouri Diagnostic Plan (Callis, 1965): lack of educational and occupational information, conflict with significant others, and lack of information about oneself. A fourth category was based on Holland, Magoon, and Spokane's (1981) speculation that career guidance instruments have beneficial effects because they provide for the "acquisition of some cognitive structure for organizing information about self, occupations, and their relations" (p. 285); this category was described as the need for cognitive structure to relate aspects of oneself to appropriate careers.…”
Section: Initial Development Of Revised Measurementioning
confidence: 99%
“…The outcome measures of counseling, client-perceived improvement and satisfaction, were obtained from the Counseling Service Assessment Blank (Hurst, Weigel, Thatcher, Nyman, 1969), a self-report questionnaire measuring the client's attitude toward the experience of counseling. The questionnaire, based in part on the Missouri Diagnostic Classification Plan (Callis, 1965), requires clients to indicate on a 6-point rating scale the degree to which the services received helped in each of five problem areas: (a) lack of information or understanding about self, (b) lack of information or understanding about the environment, (c) conflict within self, (d) conflict with significant others, and (e) lack of a specific skill. Client-perceived improvement was measured by client ratings of these problem areas with two measures obtained for each client: the rating given the primary problem area and the total ratings for all other related problem areas.…”
Section: Measurement Of Variablesmentioning
confidence: 99%